2018
DOI: 10.16970/entoted.424746
|View full text |Cite
|
Sign up to set email alerts
|

Spinosad resistance in a population of Frankliniella occidentalis (Pergande, 1895) from Antalya and its cross resistance to acrinathrin and formetanate

Abstract: Spinosad resistance in a population of Frankliniella occidentalis (Pergande, 1895) from Antalya and its cross resistance to acrinathrin and formetanate 1 Antalya'dan alınan bir Frankliniella occidentalis (Pergande, 1895) popülasyonunda spinosad direnci ve bu popülasyonun acrinathrin ve formetanate'a karşı çapraz direnci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Thrips, especially F. occidentalis, have developed resistance to a large number of pesticides (Jensen, 2000;Gao et al, 2012). Insecticide resistance in this pest thrips has been well documented for several insecticide groups, including spinosad (Bielza et al, 2007;Bielza, 2008;Zang et al, 2008;Dong-gang, 2016;Dağlı, 2018). Therefore, alternative methods of control should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Thrips, especially F. occidentalis, have developed resistance to a large number of pesticides (Jensen, 2000;Gao et al, 2012). Insecticide resistance in this pest thrips has been well documented for several insecticide groups, including spinosad (Bielza et al, 2007;Bielza, 2008;Zang et al, 2008;Dong-gang, 2016;Dağlı, 2018). Therefore, alternative methods of control should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…As Tunç & Hastenpflug-Vesmanis (2016) reported, F. occidentalis seems to have become the predominant thrips species on many crops and wild plants in Turkey. It is thought that one of the reasons of this population growth is the increasing resistance of the pest to the pesticides used for control (Dağlı, 2018). Onion thrips, T. tabaci is known to feed on many vegetable species and field crops as well as on a wide variety of weeds (Doederleini & Sites, 1993).…”
Section: Chirothrips Aculeatusmentioning
confidence: 99%
“…Numerous studies associated with this issue in various countries have shown that many population of this thrips species have gained resistance to not only organic chlorine, organophosphorus, carbamate and pyrethroid classes but also new generation bioinsecticides classes such as avermectin and spinosyn (Immaraju et al, 1992;Brodsgaard, 1994;Jensen, 1998;Kontsedalov et al, 1998;Jensen, 2000;Espinosa et al, 2002;Herron & James, 2005;Bielza et al, 2007;Thalavaisundaram et al, 2008;Zhang et al, 2008;Gao et al, 2012;Sparks et al, 2012;Dong-Gang et al, 2016;Dağlı, 2018;Cubillos-Salamanca et al, 2019;APRD, 2022). Frankliniella occidentalis was the first detected in Türkiye in 1993 (Tunç & Göçmen, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These two insecticides are derivatives of biologically active ingredient produced by Saccharopolyspora spinosa Mertz & Yao, 1990, and these spinosyn compounds are considered to have a low environmental risk (Bacci et al, 2016). However, in a previous study, a high level of spinosad resistance (235 times) to F. occidentalis was detected in one location (Kumluca) in 2015 (Dağlı, 2018). Due to their considerable safety, use of spinosad, and spinetoram have expanded in agricultural areas in the region recently by obtaining recommendations against important pests in vegetables, industrial plants, vineyards and various fruits (Anonymous, 2022c).…”
Section: Introductionmentioning
confidence: 99%